Answer:
The initial height of the base ball based on the equation for the height of the base ball, [tex]h = -16t^2 + 32t + 3[/tex] is 3 ft
Step-by-step explanation:
For clarity, if we put the equation of the height of the base ball as
[tex]h = -16t^2 + 32t + 3[/tex]
Then the initial height of the base ball will be at the point t = 0
That is
[tex]h = -16(0)^2 + 32(0) + 3[/tex] or
h = 3 ft
The initial height of the base ball based on the equation for the height of the base ball, [tex]h = -16t^2 + 32t + 3[/tex] is then = 3 ft.